MINIMALIST GARDEN DESIGN IN BUILDING ENGINEERING EDUCATION STUDY PROGRAM, PALANGKA RAYA UNIVERSITY - Sri Nadila Amriyana; Petrisly Perkasa (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2021)
This study aims to create a garden landscape design with a minimalist design in the Building Engineering Education Study Program Building. The existence of a good, comfortable, and cool garden can have a good influence on its users. Parks can be a place for socializing, studying, doing research or just resting and taking shelter. The reason for choosing a garden design with a minimalist concept is based on the main building which has a similar concept and a minimalist concept and is a concept that tends to be more modern and economical with dynamic, firm and simple design characteristics. The research begins with a search for references, then field research in the form of surveys and measurements, then sketches and pre-design plans are made to find the right design until it becomes the design that is used as the agreed design. Design drawings consist of 2D and 3D images. Garden design consists of garden elements of soft materials in the form of plants, especially endemic plants of Kalimantan and garden elements of hard materials in the form of natural stone slabs used as walkways or rock ornaments to beautify gardens, fences or walls, pieces wood, street lamps and pergolas.